2018
DOI: 10.1128/genomea.00280-18
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Ebrios, a Novel T7virus Isolated from the Ebrie Lagoon in Abidjan, Côte d’Ivoire

Abstract: The lytic Escherichia coli phage Ebrios was isolated from a water sample collected in Ebrie Lagoon on the Adiopodoumé River in Abidjan (Republic of Côte d’Ivoire, West Africa). The linear genome of this Podoviridae family member contains 39,752 bp, has a G+C content of 52.9%, is composed of 53 open reading frames, and is related to the Stenotrophomonas maltophilia phage IME15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Coliphages in general are one of the most sequenced phage types with ~450 complete phage genomes within Genbank, isolated from a variety of sources including animal faeces (Niu et al, ; Smith et al, ; Sazinas et al, ; Golomidova et al, ), human faeces (Dalmasso et al, ), urine (Malki et al, ), river water (Alijošius et al, ), agricultural surface waters (Liao et al, ), lagoons (Ngazoa‐Kakou et al, ), sewage (Trotereau et al, ) and animal slurries (Sazinas et al, ). However, much less is known about the genetic diversity of coliphages in seawater.…”
Section: Introductionmentioning
confidence: 99%
“…Coliphages in general are one of the most sequenced phage types with ~450 complete phage genomes within Genbank, isolated from a variety of sources including animal faeces (Niu et al, ; Smith et al, ; Sazinas et al, ; Golomidova et al, ), human faeces (Dalmasso et al, ), urine (Malki et al, ), river water (Alijošius et al, ), agricultural surface waters (Liao et al, ), lagoons (Ngazoa‐Kakou et al, ), sewage (Trotereau et al, ) and animal slurries (Sazinas et al, ). However, much less is known about the genetic diversity of coliphages in seawater.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported isolating bacteriophages from wastewater (18,19). They are usually detected by lytic activity on the host bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…To establish a phage biobank for biocontrol purposes in Côte d’Ivoire, new phages are being isolated and characterized ( 1 3 ). Escherichia phages Carena and JoYop were previously isolated from the samples collected in Ebrié Lagoon (latitude 5.356322; longitude −4.091498) and in wastewater of Yopougon (latitude 5.327334; longitude −4.028653), respectively ( 1 ).…”
Section: Announcementmentioning
confidence: 99%